Acute Colonic Pseudo-Obstruction with Feeding Intolerance in Critically Ill Patients: A Study according to Gut Wall Analysis - Chenyan Zhao; Tingbin Xie; Jun Li; Minhua Cheng; Jialiang Shi; Tao Gao; Fengchan Xi; Juanhong Shen; Chun Cao; Wenkui Yu (Gastroenterology Research and Practice)
Objective. To compare the differences between acute colonic pseudo-obstruction (ACPO) with and without acute gut wall thickening. Methods. ACPO patients with feeding tolerance were divided into ACPO with no obvious gut wall thickening (ACPO-NT) group and ACPO with obvious acute gut wall thickening (ACPO-T) group according to computed tomography and abdominal radiographs. Patients’ condition, responses to supportive measures, pharmacologic therapy, endoscopic decompression, and surgeries and outcomes were compared. Results. Patients in ACPO-T group had a significantly higher APACHE II (11.82 versus 8.25, p=0.008) and SOFA scores (6.47 versus 3.54, p<0.001) and a significantly higher 28-day mortality (17.78% versus 4.16%, p=0.032) and longer intensive care unit stage (4 versus 16 d, p<0.001). Patients in ACPO-NT group were more likely to be responsive to supportive treatment (62.50% versus 24.44%, p<0.001), neostigmine (77.78% versus 17.64%, p<0.001), and colonoscopic decompression (75% versus 42.86%, p=0.318) than those in ACPO-T group. Of the patients who underwent ileostomy, 81.25% gained benefits. Conclusions. ACPO patients with gut wall thickening are more severe and are less likely to be responsive to nonsurgical treatment. Ileostomy may be a good option for ACPO patients with gut wall thickening who are irresponsive to nonsurgical treatment.